2021
DOI: 10.1136/bmjopen-2020-045923
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to care for migrant children and young people with mental health problems and/or neurodevelopmental differences in high-income countries: a meta-ethnography

Abstract: ObjectivesTo develop conceptual understanding of perceived barriers to seeking care for migrant children and young people (aged 0–25 years) with mental health problems and/or neurodevelopmental differences in high-income countries.DesignQualitative evidence synthesis using meta-ethnography methodology. We searched four electronic databases (Medline, PsycINFO, Global Health and Web of Science) from inception to July 2019 for qualitative studies exploring barriers to care (as perceived by migrant communities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…A large limitation of the study was the lack of additional relevant variables for assessing health-care utilization. Research has pointed out the complexities of needs and utilization of care, and the circular process of care-seeking rather than a linear relationship between need and utilization (Place et al , 2021). This corresponds to both supply-side factors, such as approachability, acceptability, availability and appropriateness, as well as demand-side factors such as ability to seek, reach and engage.…”
Section: Discussionmentioning
confidence: 99%
“…A large limitation of the study was the lack of additional relevant variables for assessing health-care utilization. Research has pointed out the complexities of needs and utilization of care, and the circular process of care-seeking rather than a linear relationship between need and utilization (Place et al , 2021). This corresponds to both supply-side factors, such as approachability, acceptability, availability and appropriateness, as well as demand-side factors such as ability to seek, reach and engage.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancies in terms of treatment receipt were larger between migrant and Swedish majority children, than between descendent and Swedish majority children, which is consistent with findings that psychiatric care use is higher among descendent refugee children compared to newly arrived refugee children (Berg et al ., 2020). Given that research has shown that migrant children may face multiple barriers to psychiatric care, including communication and cultural barriers, as well as limited knowledge of the mental health care system among parents (Place et al ., 2021), it is conceivable that families with children who are born in Sweden may be better able to navigate the mental health care system and to overcome barriers, compared to more recently arrived migrant families. Lack of knowledge of the Swedish language should not formally restrict the receipt of certain types of treatments, such as psychotherapy, which should be offered with the help of interpreters, but such obstacles may of course nonetheless exist.…”
Section: Discussionmentioning
confidence: 99%
“…Immigrant parents may be less likely to accept psychotropic drug treatments compared to the majority parents (Guzder et al ., 2013), while psychotherapy adapted to transcultural encounters may better meet the needs of migrant children (Grau et al ., 2020). Most studies, however, have focused on barriers to accessing care, and therefore, we do not know how saliently reported barriers such as stigma, language obstacles, lack of knowledge of services, perceived lack of cultural sensitivity among providers, etc., (Place et al ., 2021) relate to the provision and/or acceptance of treatments for those who overcome barriers to accessing care.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this elevated morbidity risk, studies consistently document how young refugees have fewer contacts with mental health services than host country youth [ 17 , 18 , 19 , 20 ]. This underutilization is explained by the complex interplay of barriers to access and engagement in mental health services for refugee communities [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%